A comprehensive review of Enviro-Exergo-economic analysis of solar stills. (October 2021) - Shoeibi, Shahin; Rahbar, Nader; Abedini Esfahlani, Ahad; Kargarsharifabad, Hadi
Abstract: Solar stills are well-known tools utilized for producing fresh water from brackish or salty water. Their easy and environmentally friendly operation and low construction cost are the main advantages of these systems. However, low amounts of water production have increased the price of freshwater in these systems. Therefore, economic analysis is the main part of every experimental and numerical study in the field of solar water desalination. Over the recent years, in addition to the economic analysis, the environmental impacts and carbon credit earn of these devices have been found to be of great importance in the solar desalination studies. This research was conducted to review different techniques used to optimize these systems considering the productivity and economic and environmental analysis. Moreover, a comprehensive attempt was made to compare the cost of fabrication, exergoeconomic analysis, CO2 mitigation, enviroeconomic analysis of various geometry and designs of these systems. Finally, a summary of the comparison between previous studies were presented and discussed in details in order to give researchers a better view of cost-effective and environmentally friendly designs of solar stills. Our results revealed that the overall water production cost of solar stills was reported to be between 0.0014 and 0.29 $/L while the highest CO2 mitigation during life time was estimated to be about 1129.53 tons in the solar still combined with photovoltaic/thermal and solar collector. Highlights: The water depth has direct affected the enviroeconomic parameters of solar still. The exergoeconomic parameter based on the exergy is lower than exergoeconomic parameter based on the energy. The annual CO2 mitigation in solar still are in the range of 0.24 tons–26.97 tones. The highest CPL is achieved in tubular solar still by using parabolic concentrator. The lowest CPL was obtained in passive solar still with phase change material.